2007
DOI: 10.1111/j.1525-1470.2007.00326.x
|View full text |Cite
|
Sign up to set email alerts
|

Benign Cutaneous Degos Disease in a 16‐Year‐Old Girl

Abstract: Degos disease is a rare disorder, characterized by the development of typical atrophic porcelain-white macules on the trunk and extremities. It most commonly occurs in middle-aged Caucasian adults and eventuates in fatality in the majority of patients. A minority of reported patients have a more benign course and a favorable outcome. Degos disease is extremely rare in children. We report Degos disease in a teenager with an extended survival and the absence of internal involvement. We discuss the concept of ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
48
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 41 publications
2
48
0
Order By: Relevance
“…The gastrointestinal system is involved in approximately 50% of cases (mostly small bowel), and intestinal necrosis, perforation and ultimately peritonitis is the most frequent (62%) cause of mortality [28]; the CNS is involved in approximately 20% of cases, but death can also be due to other affected systems, including cardiopulmonary [25,29 ]. Pediatric cases have been reported, ages ranging from birth to 18 years, with a mortality rate of 58% resulting from vascular disease of the gastrointestinal and CNS systems, or either of the two individually, in all cases reviewed by Wilson et al [30 ]. Wilson et al [30 ] also found 34 well-documented cases of a Degos' disease variant termed benign cutaneous Degos' disease, in which only the skin is involved.…”
Section: Degos' Diseasementioning
confidence: 91%
See 1 more Smart Citation
“…The gastrointestinal system is involved in approximately 50% of cases (mostly small bowel), and intestinal necrosis, perforation and ultimately peritonitis is the most frequent (62%) cause of mortality [28]; the CNS is involved in approximately 20% of cases, but death can also be due to other affected systems, including cardiopulmonary [25,29 ]. Pediatric cases have been reported, ages ranging from birth to 18 years, with a mortality rate of 58% resulting from vascular disease of the gastrointestinal and CNS systems, or either of the two individually, in all cases reviewed by Wilson et al [30 ]. Wilson et al [30 ] also found 34 well-documented cases of a Degos' disease variant termed benign cutaneous Degos' disease, in which only the skin is involved.…”
Section: Degos' Diseasementioning
confidence: 91%
“…Pediatric cases have been reported, ages ranging from birth to 18 years, with a mortality rate of 58% resulting from vascular disease of the gastrointestinal and CNS systems, or either of the two individually, in all cases reviewed by Wilson et al [30 ]. Wilson et al [30 ] also found 34 well-documented cases of a Degos' disease variant termed benign cutaneous Degos' disease, in which only the skin is involved. They found that patients with this benign form were on average 37.6 years old and that there were 3.25 as many women as men, a reversal of the ratio found in the systemic variant.…”
Section: Degos' Diseasementioning
confidence: 91%
“…13 The gastrointestinal tract is the most frequently involved internal organ, and usually presents with acute, severe abdominal pain. 2,6,13 The central nervous system is affected in approximately 20% of patients, with reported manifestations including parasthesias, headaches, hemiplegia, strokes, epilepsy, or nonspecific neurological symptoms. 14 Common causes of death include sepsis from peritonitis and hemorrhagic or ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…3 The pathognomonic features in both the benign cutaneous and systemic forms of malignant atrophic papulosis are erythematous to pink papules of 2 to 15 mm in diameter that develop central porcelain-white, atrophic scars. The papules are often surrounded by a telangiectatic rim, may be dome-shaped and occasionally form a clover-like pattern.…”
Section: Discussionmentioning
confidence: 99%